Implementing Student-Centered Collaborative Learning when Teaching Productive Skills in An ESL Primary Classroom - Nasir, Nurul Athirah Mohd; Aziz, Azlina Abd. (International Journal of Publication and Social Studies, 2020)
The English language plays a crucial role in serving its purposes in various fields such as in the education system, business and economy because of its standard as an international language. Young English language learners often face difficulties in mastering the English language productive skills which are the speaking and writing skills. Therefore, English language educators often apply 21st century teaching styles aim to enhance learners’ ESL language learning which include collaborative learning for young learners. This qualitative case study aims to explore Malaysian teachers’ perceptions on the implementation of the student-centered collaborative learning in the teaching of productive skills namely the speaking and writing skills in a Malaysian ESL primary classroom. Specifically, the study focuses on how the ESL teachers implement collaborative learning, the effective ways of implementing collaborative learning as well as the challenges they encountered during the implementation of the student-centered collaborative learning. Document analysis, observation and interviews are employed as the research instruments. Findings revealed that assigning learners’ roles, group evaluation, the application of differentiated instruction as well as assigning more language-based, personal-response and stylistic activities are the teachers’ current practices in promoting the collaborative learning. This study found out the effective ways of implementing the collaborative learning are by assigning learners’ roles, use of teaching aids, evaluation of the learning process and products as well as providing more language-based activities whereas classroom management is proven to be the main obstacle faced.